2009
DOI: 10.2478/s11535-008-0051-4
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the human nuclear chromatin induced by ultra wideband pulse irradiation

Abstract: The effects of ultra wideband pulse radiation on human cells were investigated. The density of the flow of energy on the surface of irradiated object varied from 10−6 to 10−2 W/cm2 with exposure of 10 s. It was shown that heterochromatin granule quantity in cell nuclei increased under the influence of radiation from 10−4 to 10−2 W/cm2. In some intervals the effect increased with irradiation dose. At irradiation intensity 10−3 W/cm2 the process of heterochromatin granule formation was fully reversible after 2 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 21 publications
(19 reference statements)
1
11
0
Order By: Relevance
“…1/2. after electromagnetic cell exposure has been shown earlier (Shckorbatov et al, 2009a;Pasiuga et al, 2009), but in this paper for the first time we test the dependence of cell recovery on the intensity of microwave exposure. …”
mentioning
confidence: 69%
See 1 more Smart Citation
“…1/2. after electromagnetic cell exposure has been shown earlier (Shckorbatov et al, 2009a;Pasiuga et al, 2009), but in this paper for the first time we test the dependence of cell recovery on the intensity of microwave exposure. …”
mentioning
confidence: 69%
“…In our previous work we demonstrated condensation of chromatin in granules induced by an electromagnetic field (Shckorbatov et al, 1998;Shckorbatov et al, 2009a;2009b), but the process of recovery of microwave induced changes in chromatin microscopic morphology has remained almost uninvestigated. We observed an effect of time after microwave exposure and power density of irradiation on degree of chromatin condensation (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…The simple method for determination of the portion of heterochromatin by counting the number of heterochromatin granules in a probe of cells and determination of average number per cell was proposed for buccal epithelium cells -cells of cheek mucosa [109]. In a series of works it was demonstrated that the low energy EMF (10 -100 µW/cm 2 ) and static magnetic field (25 mT) induce chromatin condensation (heterochromatinization) [38,47,[110][111][112][113][114]. It is supposed that this phenomenon reflects the process of regulation of genetic activity at cytological level, because heterochromatinization is connected with decrease of functional activity of chromatin [115,116].…”
Section: The Action Of Emf On Intracellular Regulatory Systemsmentioning
confidence: 99%
“…The intensity of UWBR was 10 -6 , 10 -5 , 10 -4 , 10 -3 , and 10 -2 W/cm 2 , exposure time -10 seconds. The experimental procedure is described in [5]. The short pulse generator formed the sequence of pulses with amplitude 25 V and a pulse duration 500 ps at the half of pulse height.…”
Section: Experimental Setup and Experimental Proceduresmentioning
confidence: 99%